Some biological aspects of Biomphalaria glabrata (Say, 1818) and Biomphalaria tenagophila (D'Orbigny, 1835) (Pulmonata, planorbidae): II - Fecundity and fertility - Kawazoe, Urara (Revista de Saúde Pública, 1977)
The fecundity (ratio egg-masses per snail, eggs per snail and eggs per egg-mass) and the fertility (hatchability and viability of eggs) of Biomphalaria glabrata and Biomphalaria tenagophila were compared during one year, in the laboratory. The average of eggs per egg-mass was significantly higher in B. glabrata (19.9) than in B. tenagophila (16.2) and both species showed highest fecundity during April. The influence of temperature was very small. The fecundity defined as egg-mass per snail per day was greater in B. glabrata (0.65) than in B. tenagophila (0.56). The same was verified in the ratio eggs per snail per day: the average was 13.4 in B. glabrata and 9.9 in B. tenagophila. Considering the fertility as percentage of snail hatchability, B. glabrata showed an average of 95.8 and B. tenagophila 90.5%, the difference being significant, at the 5% level. The greatest hatchability rate in B. glabrata was observed during November-January (98.0); in B. tenagophila, during October-November (95.0%). Seasonal rhythm and influence of seasonal variation of temperature were not observed.